(untitled) (Journal of Life and Earth Science, 2011)
To identify the factors contributing to the farmers’ attitude towards Integrated Pest Management (IPM) practices in rice cultivation, 158 family heads of the Farmers Field Schools (FFSs) at Godagari Upzila under Rajshahi District were chosen at random to constitute the subjects of the study. Data were collected from 5 September, 2006 to 28 January, 2007. Twenty four selected characteristics of the farmers were considered as the independent variables while the attitude towards IPM practices in rice cultivation was the only dependent variable. Chi-square tests revealed that all variables except age, family size, farm size, supervision of crop production, annual income and peer relationship differed significantly with the attitude of the farmers. Stepwise multiple regression analysis indicated that aspiration alone contributed more than three-fifths (65.10%) of the total variation, whereas knowledge about pests, predators and risk orientation had also considerable contribution to the attitude towards IPM practices. Results of the path co-efficient analysis showed that aspiration, knowledge about pests and predators, risk orientation, mass extension contact and communication exposure had strong direct and indirect effects on the attitude of the farmers towards IPM practices in rice cultivation in the study area. Key words: Contributing variables; farmers’; attitude; IPM; rice cultivation; Barind. DOI: 10.3329/jles.v5i0.7342 J. Life Earth Sci., Vol. 5: 11-15, 2010